Fabrication and characterization of polyaniline /polyvinyl alcohol conducting blend films / Sakhawi Muhsin Samsukamar - Samsukamar, Sakhawi Muhsin (Faculty of Applied Sciences, 2017)
Conducting blend films of polyaniline (PANI)/polyvinyl alcohol (PV A) formed by ex-situ chemical oxidative polymerization reaction with used of hydrochloric acid (HCl) as a dopant, sorbitan monolaurate (Tween 20) as surfactant and potassium persufate (KPS) as oxidation agent. P ANI shown good dispersion in PV A polymeric matrix and less precipitation were found. Films do not conduct electricity due to P ANI exist in form of emeraldine base and prove with no absorbance peak that found in UV-Vis spectroscopy analysis due to random error that be done in methodology.